Diaphanous-related formin mDia2 regulates beta2 integrins to control hematopoietic stem and progenitor cell engraftment - Yang Mei (Nature Portfolio, 2020)
Bone marrow engraftment of haematopoietic stem and progenitor cells (HSPCs) requires homing and lodgement to the niche. Here, the authors show that mDia2 is required for HSPC polarization, nuclear MAL, and SRF-induced beta2 integrin expression during transendothelial migration of HSPCs required for engraftment.